BREEDING AND CULTIVATION OF TILAPIA IN FISH FARMS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article is important for the development of industrial requirements and conditions of the Republic of Uzbekistan for ensuring the population's need for cheap and quality meat production.